190 Opposite profiles of complement in antiphospholipid syndrome (APS) and systemic lupus erythematosus (SLE) among patients with antiphospholipid antibodies. (April 2019) - Yu, Chack-Yung; Savelli, Stephanie; Roubey, Robert; Kitzmiller, Kathryn; Zhou, Danlei; Nagaraja, Haikady; Mulvihill, Evan; Barbar-Smiley, Fatima; Ardoin, Stacy P; Wu, Yee-Ling
Abstract : Background: Antiphospholoipid syndrome (APS) is the association of antiphospholipid antibodies (aPL) with thromboses and/or recurrent pregnancy loss (RPL). Among patients with SLE, one-third have aPL and 10%–15% have a manifestation of secondary APS. Although mouse models suggested complement drives the pathogenesis of APS, we have little knowledge on how complement proteins and genes contribute to the pathology of human APS, and the concurrence of SLE and APS. Methods: We performed a cross-sectional study on complement proteins and genes in 525 patients with aPL. Among them, 237 experienced thromboses and 293 had SLE; 111 had both SLE and thromboses, and 106 had neither SLE nor thrombosis. Complement protein levels were determined by radial immunodiffusion for C4, C3 and factor H; and by functional ELISA for mannan binding lectin (MBL). Total C4, C4A and C4B gene copy numbers (GCN) were measured by TaqMan-based realtime PCR. Results: Two to six copies of C4 genes are frequently present in a diploid genome, and each copy may code for an acidic C4A or a basic C4B protein. We observed significantly (a) higher protein levels of total C4, C4A, C4B, C3 and anticardiolipin (ACLA) IgG, (b) increased frequencies of lupus anticoagulant and males, and (c) depressed levels of complement factor H, MBL and ACLA-IgM among patients with thrombosis than those without thrombosis (n=288). We also observed significantly lower GCNs of total C4 and C4A among aPL-positive patients with both SLE and thrombosis than others. By contrast, aPL-positive subjects with SLE had significantly reduced protein levels of C3, total C4, C4A, C4B and ACLA-IgG, and higher frequency of females than those without SLE. Patients with thrombosis but without SLE (n=126), and patients with SLE but without thrombosis (n=182) had the greatest differences in mean protein levels of C3 (p=2.6×10–6), C4 (p=2.2×10–9) and ACLA-IgG (p=1.2×10–5). RPL occurred in 23.7% of female patients and thrombotic SLE patients had the highest frequency of RPL (41.0%; p=3.8×10–10). Compared with non-RPL females, RPL had significantly higher frequency of thrombosis and elevated C4 protein levels. Female patients with homozygous C4A deficiency all experienced RPL (p=0.0001) but the opposite was true for patients with homozygous C4B deficiency (p=0.017). Conclusions: There are substantial differences for complement protein concentrations and genetic diversities among aPL-positive patients with thromboses, recurrent pregnancy loss and SLE. These results are relvant for diagnosis and management of APS and SLE. Funding Source(s): This work was supported by NIH grants 1 R01 AR050078, 1 R21070905, 1 R01 AR073311 (CYY), and RR00046 (UNC).